Effect of Hydrophobic Polymers on the Gastro Retention Time and In vitro Release of Ciprofloxacin HCl from Co-matrix Tablets - Islam, Muhammad Shahidul; Sutradhar, Kumar Bishwajit; Chowdhury, Jakir Ahmed; Reza, Md Selim (Dhaka University Journal of Pharmaceutical Sciences, 2011)
The present study was conducted to investigate the effect of different polymers on the release profile and bio-adhesive strength of a water soluble drug, ciprofloxacin HCl from different percentages of Eudragit RS PO and Kollidon SR based co-matrix tablets. Matrix formulations were prepared by direct compression method. The bioadhesive property was investigated in terms of retention time following in vitro wash-off method. The concentrations of polymers were varied to investigate whether these variations can cause any change in release of ciprofloxacin HCl molecule and bio-adhesion property or not. In most of the cases it is found that Eudragit RS PO based co-matrix tablets release greater percentage of active drug and that bio-adhesive strength of Kollidon SR and xanthan gum based co-matrix tablets were significantly better. Finally it was revealed that xanthan gum provided optimum bioadhesion functioning as a synergist in co-matrices and comply the USP specification as a most suitable controlled release polymer. Key words: Gastro retention time; direct compression; ciprofloxacin HCl; Eudragit RS PO; Kollidon SR; xanthan gum. DOI: http://dx.doi.org/10.3329/dujps.v9i2.7893 Dhaka Univ. J. Pharm. Sci. 9(2): 97-102, 2010 (December)